Influence of communication tools on customer behaviour within a food product after declared consumption date in global - Mráček, Pavel; Milichovský, František (EDP Sciences, 2021)
Research background: Marketing communication should catch the attention of target customers, who pay attention to advertisements to make an interest in product, service, brand, or company. Marketing communication can impact customers behaviour in food choice due to association with personal identity, which is important interpersonal communication to others. Purpose of the article: Customers purchase a lot of food with no matter the possibility of consumption. Therefore, a lot of foods are wasted or degraded for consumption, because of health risks. It is necessary to influence target customers and change their mind setup and their purchasing behaviour in global retail chains. Methods: As primary research, a questionnaire survey was used. For the survey was asked 1042 persons to participate. From asked persons, we receive 451 questionnaires, which mean 43,28 %. In the amount of returned questionnaires, we had to remove 23 lists as incomplete. The total complete forms were 428 (41,08 % of asked). For the evaluation of gained data, there was applied Pearson’s chi-square test for independence of variables. Findings & Value added: Customers behave according to the presented message in communication tools, which they believe. Therefore, it is possible to use communication tools on the way of recipient behaviour cultivation. The main objective of the paper is to find a connection between marketing communication tools and customer behaviour within food products after the declared consumption date. For evaluation, there were used five variables of customer behaviour with food, and seven chosen marketing communication tools. From 35 possible connections, we found out dependencies for ten relations.

Research background: Marketing communication should catch the attention of target customers, who pay attention to advertisements to make an interest in product, service, brand, or company. Marketing communication can impact customers behaviour in food choice due to association with personal identity, which is important interpersonal communication to others. Purpose of the article: Customers purchase a lot of food with no matter the possibility of consumption. Therefore, a lot of foods are wasted or degraded for consumption, because of health risks. It is necessary to influence target customers and change their mind setup and their purchasing behaviour in global retail chains. Methods: As primary research, a questionnaire survey was used. For the survey was asked 1042 persons to participate. From asked persons, we receive 451 questionnaires, which mean 43,28 %. In the amount of returned questionnaires, we had to remove 23 lists as incomplete. The total complete forms were 428 (41,08 % of asked). For the evaluation of gained data, there was applied Pearson’s chi-square test for independence of variables. Findings & Value added: Customers behave according to the presented message in communication tools, which they believe. Therefore, it is possible to use communication tools on the way of recipient behaviour cultivation. The main objective of the paper is to find a connection between marketing communication tools and customer behaviour within food products after the declared consumption date. For evaluation, there were used five variables of customer behaviour with food, and seven chosen marketing communication tools. From 35 possible connections, we found out dependencies for ten relations.
Influence of communication tools on customer behaviour within a food product after declared consumption date in global
Keywords: marketing communication tools; food product; date of consumption; global retail; customer behavior; marketing communication tools; food product; date of consumption; global retail; customer behavior